2022
DOI: 10.1021/acs.analchem.1c04748
|View full text |Cite
|
Sign up to set email alerts
|

All-Solid-State Polymeric Membrane Ion-Selective Electrodes Based on NiCo2S4 as a Solid Contact

Abstract: The performance criteria for the design of all-solid-state ion-selective electrodes mainly include high electrode-to-electrode reproducibility and a low potential drift. Here, we introduce nickel cobalt sulfide (NiCo2S4) as a solid contact for ion-to-electron transduction based on multiple redox couples. NiCo2S4 materials with different morphologies can be prepared through a facile hydrothermal/solvothermal method. A NiCo2S4-based solid-contact Ca2+-ISE has been developed, which exhibits a Nernstian slope of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…In the case of MoS 2 and SnS 2 , 0.5 < b < 1, indicating that the electrochemical process is controlled by diffusion. However, in the SnS 2 -MoS 2 , the electrochemical process is surface-controlled (b ≈ 1) (Figure f), which can be attributed to the rapid electron transfer at the heterogeneous interface, leading to increased material capacitance . Detailed CV curves at different sweep speeds can be seen in Figure S6.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of MoS 2 and SnS 2 , 0.5 < b < 1, indicating that the electrochemical process is controlled by diffusion. However, in the SnS 2 -MoS 2 , the electrochemical process is surface-controlled (b ≈ 1) (Figure f), which can be attributed to the rapid electron transfer at the heterogeneous interface, leading to increased material capacitance . Detailed CV curves at different sweep speeds can be seen in Figure S6.…”
Section: Resultsmentioning
confidence: 99%
“…37 The potential drift value of the GC/SnS 2 -MoS 2 /Na + -ISM electrode is 1.43 μV/s, and those of the GC/MoS 2 /Na + -ISM and GC/SnS 2 /Na + -ISM are 7.05 and 79.15 μV/s, respectively. The capacitance (C) value is determined through the approximate equation ΔE/Δt = i/ C. 36 The findings indicate that the capacitance of GC/SnS 2 -MoS 2 /Na + -ISM is 699 μF, which is significantly higher than those of GC/MoS 2 /Na + -ISM (142 μF) and GC/SnS 2 /Na + -ISM (12 μF). Moreover, it surpasses the capacitance of polymer and nanomaterial transduction layers reported in Table 1, indicating that using heterojunction materials to design high capacity and high hydrophobic ion-electron transduction layer materials is an effective method.…”
Section: ■ Materials and Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Recently, Li, Qin and coworkers utilized nickel cobalt sulfide (NiCo 2 S 4 ) as the solid contact for ion-to-electron transduction to develop an all-solid-state polymeric membrane Ca 2+ -ion selective electrode. 41 The synergistic effect of nickel and cobalt ions contributed to the increased redox capacitances of NiCo 2 S 4 , through the redox reactions of Ni 3+ /Ni 2+ and Co 4+ /Co 3+ /Co 2+ redox couples. Following this work, the same authors reported the in situ preparation of quasi-superhydrophobic porous NiCo 2 S 4 nanosheet arrays via one-step electrodeposition and used the prepared NiCo 2 S 4 nanosheet arrays as the solid contact to construct a Ca 2+ -ion selective electrode.…”
mentioning
confidence: 99%
“…Due to good hydrophobicity, excellent conductivity, and large redox capacitance, NiCo 2 S 4 has been synthesized and used as an ion-to-electron transducer for preparation of all-solid-state potentiometric sensors in our previous research. , The presence of the nanostructured NiCo 2 S 4 solid contact not only effectively suppresses the formation of a water layer at the sensing membrane/NiCo 2 S 4 interface but also largely improves the sensor stability and reproducibility. The in situ formed NiCo 2 S 4 nanowire arrays can act as a “superhighway” for ultrafast ion/electron transport and provide a large surface area, redox capacitance, and abundant availability of electrochemical active sites, thus yielding a high potential stability.…”
mentioning
confidence: 99%